Industry Specifics and Consumers’ Reactions to Business Crises - Kazlauskienė Asta (Economics and Business)
Different scientific studies provide many valuable recommendations how to manage crises in order to lessen their negative effect on relations with consumers. But the question whether the same business crises management rules can be applied for different industries, or they must be adapted depending on industries specifics, has not received sufficient scientific attention. Knowledge gaps about industry specific effect on consumer reactions to business crises remain. This study focuses on understanding the differences in consumers’ reactions in business crises situations with regard to controversial evaluation in the society of “the sin industries” (alcohol, tobacco, gambling, etc.) and ordinary industries (not having controversial associations). Experimental research design, including online experiment with tobacco, beer and functional soft drinks consumers (in total 306 respondents), was chosen for competing research hypotheses testing. Empirical evidence was in line with theoretical argumentation about less negative consumers’ reactions during business crises in case of “sin industries” versus ordinary industry. This study shows that consumers attitudes, such as perception of company’s product quality, trust, social responsibility and behavioural intentions, such as intention to buy and recommend company’s products, are less negative during business crises in lower reputation “sin industries” than in ordinary industries.